Saya ou l’impossible virtuosité - Zaven Paré (Ateliers d'Anthropologie)
Saya is the name of an anthropomorphic robot developed by Professor Kobayashi of Tokyo University. The Professor demonstrates here his robot-teacher before a class of students. This demonstration gone wrong provides the starting point for the author to reflect on the virtuosity of machines. He questioned the link maintained by the Saya demonstration with the Turing Test and the ambiguity between man and machine that haunts every demonstration in robotics. A relationship is established here, during the demonstration, with the public in which everyone seems to agree voluntarily on the fact that what is fake must look real. The observation of a failed demonstration is a tremendous opportunity to capture the way robotics demonstrations need this ontological confusion (between man and machine) to produce effects of virtuosity.